Downregulation of MicroRNA-126 Contributes to the Failing Right Ventricle in Pulmonary Arterial Hypertension. Issue 10 (8th September 2015) - Potus, François; Ruffenach, Grégoire; Dahou, Abdellaziz; Thebault, Christophe; Breuils-Bonnet, Sandra; Tremblay, Ève; Nadeau, Valérie; Paradis, Renée; Graydon, Colin; Wong, Ryan; Johnson, Ian; Paulin, Roxane; et al.
<x xml:space="preserve">Abstract</x> Background— Right ventricular (RV) failure is the most important factor of both morbidity and mortality in pulmonary arterial hypertension (PAH). However, the underlying mechanisms resulting in the failed RV in PAH remain unknown. There is growing evidence that angiogenesis and microRNAs are involved in PAH-associated RV failure. We hypothesized that microRNA-126 (miR-126) downregulation decreases microvessel density and promotes the transition from a compensated to a decompensated RV in PAH. Methods and Results— We studied RV free wall tissues from humans with normal RV (n=17), those with compensated RV hypertrophy (n=8), and patients with PAH with decompensated RV failure (n=14). Compared with RV tissues from patients with compensated RV hypertrophy, patients with decompensated RV failure had decreased miR-126 expression (quantitative reverse transcription–polymerase chain reaction; P<0.01) and capillary density (CD31+ immunofluorescence; P<0.001), whereas left ventricular tissues were not affected. miR-126 downregulation was associated with increased Sprouty-related EVH1 domain-containing protein 1 (SPRED-1), leading to decreased activation of RAF (phosphorylated RAF/RAF) and mitogen-activated protein kinase (MAPK); (phosphorylated MAPK/MAPK), thus inhibiting the vascular endothelial growth factor pathway. In vitro, Matrigel assay showed that miR-126 upregulation increased angiogenesis of primary cultured endothelial cells from patients with decompensated RV failure. Furthermore, in vivo miR-126 upregulation (mimic intravenous injection) improved cardiac vascular density and function of monocrotaline-induced PAH animals. Conclusions— RV failure in PAH is associated with a specific molecular signature within the RV, contributing to a decrease in RV vascular density and promoting the progression to RV failure. More importantly, miR-126 upregulation in the RV improves microvessel density and RV function in experimental PAH.